Reference values of nuchal fold thickness in an Iranian population sample - Kimia Kazemi; Atoosa Adibi; Silva Hovsepian (Journal of Research in Medical Sciences, 2018)
Background: Considering that ethnicity and gestational age (GA) could affect the value of nuchal fold thickness (NFT) in mid-trimester, we aimed to determine the reference intervals of NFT values for each gestational week from 16 to 24 weeks of pregnancy among a group of Iranian pregnant women. Materials and Methods: In this cross-sectional study, medical files of pregnant women who underwent fetal anomaly scanning at 16–24 weeks of gestation were reviewed and the following data were extracted: GA, value of NFT, value of nuchal translucency (NT) in their previous ultrasound study, if available, and head circumference (HC). The 5th, 25th, 50th, 75th, and 95th percentiles of NFT for each gestational week were determined. The association between NFT and HC, GA, and NT were also determined. Results: Medical files of 882 pregnant women were studied. The expected 95th percentile value of NFT between 16th and 24th weeks of gestation ranged from 4 mm to 5.9 mm. The mean (standard deviation) of NFT increased with GA from 2.67 (0.90) mm at 16th weeks to 4.69 (0.71) mm at 24th weeks. There was a significant positive association between NFT and GA (β = 1.11, p < 0.001), HC (β = 0.21, p < 0.001), and NT (β = 0.351, p < 0.001). Conclusion: The findings of this study revealed that before the 20th week of gestation, the appropriate cutoff value of NFT is 5 mm, and for 21st to 24th weeks, the proper cutoff is 6 mm. However, for providing more conclusive results, further studies with larger sample size and considering the impact of other influencing variables are recommended.